Niche Overlap Determination Through Habitat Suitability Models: A Management Tool for Native Birds of the Argentinean Pampas - Pedrana, Julieta; Bernad, Lucía; Maceira, Nestor Oscar; Isacch, Juan Pablo (BioOne, 2024)
In Argentina, predominantly in the Pampas ecoregion, the natural rangelands have increasingly been replaced by crops. Avifaunal studies have shown that the population density of several species decreased as the proportion of cropland in the landscape increased. The Greater Rhea Rhea americana and two migratory sheldgeese: the Upland Goose Chloephaga picta and Ashy-headed Goose Chloephaga poliocephala, are medium-large native species that have been common and sympatric inhabitants of the Pampas ecoregion. We aimed to analyse and compare the current ecological niches occupied by the three species during the non-breeding season in the southern Pampas of Argentina, the region where their original distributions overlapped, using Ecological Niche Factor Analysis. The three species showed high global marginality values, indicating that they occupied only a specific subset of environmental conditions of those available across the region. Suitable areas for Greater Rhea were located in the west and south of the study area, overlapping grazing lands and native habitats. The three species responded to landscape composition and configuration, as indicated by the low proportion of areas with suitable conditions for these medium-large birds. Suitable areas for Ashyheaded and Upland Geese were especially concentrated in the eastern part of the area and suitable areas for Upland Goose were more widespread than those suitable for the Ashy-headed Goose. We provide compelling evidence of low overlap between the ecological niches of the three species in the southern Pampas, which highlights the need for specific management strategies to ensure the conservation of these emblematic species. —Pedrana, J., Bernad, L., Maceira, N.O. & Isacch, J.P. (2018). Niche overlap determination through habitat suitability models: a management tool for native birds of the Argentinean Pampas.